Immunotherapy: Artificial Engineered Natural Killer Cells Combined with Antiheat Endurance as a Powerful Strategy for Enhancing Photothermal‐Immunotherapy Efficiency of Solid Tumors (Small 42/2019). Issue 42 (15th October 2019) - Zhang, Da; Zheng, Youshi; Lin, Ziguo; Lan, Shanyou; Zhang, Xiaolong; Zheng, Aixian; Li, Juan; Liu, Gang; Yang, Huanghao; Liu, Xiaolong; Liu, Jingfeng
Abstract : Photothermal therapy (PTT) has been pre‐clinically used in cancer treatment, but incomplete tumor removal and heat endurance of tumor cells could induce significant tumor relapse. In article number1902636, Xiaolong Liu, Jingfeng Liu, and co‐workers report a programmable antitumor strategy that combines artificially engineered natural killer cells with anti‐heat endurance of DNAzyme as a powerful adjuvant for immuno‐enhancing the therapeutic efficiency of PTT.